Transabdominal sacrocolpopexy with autologous rectus fascia graft. Issue 8 (August 2016) - Abraham, Nitya; Quirouet, Adrienne; Goldman, Howard
Abstract Introduction and hypothesis Extrusion and infection are potential postoperative complications when using synthetic mesh for abdominal sacrocolpopexy. Long-term follow-up in the Colpopexy and Urinary Reduction Efforts (CARE) trial revealed an estimated 9.9 % risk of mesh extrusion. There are 26 reports of spondylodiscitis after sacrocolpopexy with synthetic mesh. These surgical risks may be decreased by using autologous fascia. To date, there have been no reports of extrusion or spondylodiscitis after using autologous fascia for sacrocolpopexy. Methods This video demonstrates transabdominal sacrocolpopexy with an autologous rectus fascia graft. A 76-year-old woman with symptomatic stage 3 prolapse also had a history of diverticulitis and sigmoid abscess requiring sigmoid colectomy with end colostomy and incidental left ureteral transection with subsequent left nephrostomy tube placement. She presented for colostomy reversal, ureteral reimplantation, and prolapse repair. Given the need for concomitant colon and ureteral reconstruction, the risk of infection was potentially higher if synthetic mesh were used. The patient therefore underwent transabdominal sacrocolpopexy with autologous rectus fascia graft. Results At 4 months' follow-up the patient reported resolution of her symptoms and on examination she had no pelvic organ prolapse. Conclusion Transabdominal sacrocolpopexy using autologous rectus fascia graft is a feasible option, especially in cases in which infection and synthetic mesh extrusion risks are potentially higher.